WAVE ATTENUATION BY A COMBINATION OF SUBMERGED-EMERGED POROUS BREAKWATER - Kumala Dewi, Rianda
Porous breakwaters play an important role in protecting our coastline. A comprehensive study on the effectiveness of the porous breakwater should be conducted before it is installed in the field. We will use a mathematical model using shallow water equation to determine the wave attenuation caused by a combination of mangroves and reefball as a submerged and emerged porous breakwater in this study. We will construct two layer model to capture both types of the breakwaters. We then solve the model analytically and numerically in order to find the wave transmission coefficient. This coefficient tells us how much damping is induced by the combined breakwaters. A validation method will be carried out to assess the correctness of our numerical model using analytical solution and experimental data. In addition, we also examine the relation between the dimensions and characteristics of both the submerged and emerged breakwaters in terms of minimizing the amplitude of the wave coming to the coast. We hope this finding may help researchers in the field of coastal protection.